1991
DOI: 10.7164/antibiotics.44.218
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of the streptovaricins: 3-Amino-5-hydroxybenzoic acid as a precursor to the meta-C7N unit.

Abstract: [Ctfr&0xj;-14C]-3-ammo-5-hydroxybenzoic acid (AHBA) has been shown to be incorporated by Streptomyces spectabilis to the extent of greater than 0. 1 %(35 : 1 dilution) in the ansamycin antibiotic streptovaricin C, the major componentof the streptovaricin complex. When[carboxy-i3C]AHBA was similarly administered, C-21 (quinone methide carbonyl at 188.3ppm) of streptovaricin C was specifically labeled (at twenty one times natural abundance). In preparation for the 13C incorporation study the 13C NMR spectrum of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
68
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(68 citation statements)
references
References 13 publications
0
68
0
Order By: Relevance
“…Later work has repeatedly confirmed the specific role of AHBA as precursor of the mC 7 N unit of various other compounds. [34][35][36][37][38][39] The biosynthetic question then raised was how AHBA was formed by a route that is related to the shikimate pathway. An important issue was whether the nitrogen of AHBA was attached to the carbon corresponding to C-3 or C-5 of shikimate.…”
Section: Historymentioning
confidence: 99%
“…Later work has repeatedly confirmed the specific role of AHBA as precursor of the mC 7 N unit of various other compounds. [34][35][36][37][38][39] The biosynthetic question then raised was how AHBA was formed by a route that is related to the shikimate pathway. An important issue was whether the nitrogen of AHBA was attached to the carbon corresponding to C-3 or C-5 of shikimate.…”
Section: Historymentioning
confidence: 99%
“…S65 †). [22][23][24] The ROESY cross-peak observed from H-26 to H-24 proposed the relative conguration at the C-26 position, but the relative conguration of C-27 remained unknown for lack of related experimental data. Thus, 1 was deduced to be a new seco-streptovaricin, namely ansavaricin A (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structure and absolute conguration of the known compound streptovaricin C had been determined by X-ray analysis of a heavy atom derivative. 19,20 Although the structure of 1 was different from that of streptovaricin C, the ROESY correlations described in Fig. 2 suggested that both of them had the same relative congura-tions at C-18, C-19, C-22, C-23, C-24 and C-25.…”
mentioning
confidence: 93%
“…S29 †). 5,20 On the basis of the above analyses, the gross structure of 1 was deduced as a new ansamycin type polyketide, for which we proposed the name ansavaricin F.…”
mentioning
confidence: 99%